Efficacy and safety of transvenous lead extraction in 108 consecutive patients: a single-centre experience. (28th December 2018) - Monsefi, Nadejda; Waraich, Harmeet Singh; Vamos, Mate; Erath, Julia; Sirat, Sami; Moritz, Anton; Hohnloser, Stefan H
Abstract: OBJECTIVES: The number of cardiac implantable electronic devices is growing worldwide because they play a relevant role in improving the survival rate in patients with specific heart diseases. Cardiac implantable electronic devices complications including infection, dysfunction or venous stenosis increase the need for the least traumatic way to explant leads. Our goal was to report the successes and procedural complication rates of transvenous lead extraction (TLE) in a consecutive series of patients. METHODS: From 2010 to 2016, 108 patients underwent TLE of 227 leads due to endocarditis ( n = 21; 19%), pocket infection ( n = 58; 54%) or lead dysfunction ( n = 29; 27%). In 98% ( n = 106) of the patients, laser-assisted lead extraction was performed. In 2% ( n = 2) of the patients, the application of a solitary locking stylet was sufficient. The patient mean age was 68 ± 14 years; 25% of the patients had previous cardiac surgery. TLE was performed a mean of 9 ± 6 years after the implantation of the existing device. RESULTS: Complete procedural success (removal of all lead material from the vascular space) was achieved in 98.7% ( n = 224), and clinical success (achievement of all clinical goals associated with the indication for lead removal and absence of major complications) was achieved in 98% ( n = 106). In 2 patients the procedure failed due to a vascular tear requiring a thoracotomy. In 1 patient, complete lead extraction was not possible due to heavy calcification (coronary-sinus lead). The 30-day mortality rate was 3.7% ( n = 4); the patients died of multiorgan failure ( n = 1), cardiac failure ( n = 1) and septicaemia ( n = 2). The procedure-related major complication rate was 2% ( n = 2). CONCLUSIONS: Laser-assisted TLE seems to be a safe and effective procedure with an acceptable complication rate.